Challenges and prospects of Islamic agriculture finance : a case study of Agrobank Malaysia - Purayil, Abdul Kadar Thayath Puthiya (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
In the recent decades, Islamic finance has set a firm foundation and exhibit remarkable growth in the financial industry around the world. Both developed and developing countries have implemented and accepted it to be a part of their financial system. Islamic finance have developed itself into different areas of financing such as housing, transportation, manufacturing and other real sectors that have a significant affluence on the economy and social activities. Islam has put forth the importance of agriculture to the entire humanity right from the beginning. Islamic history has also witnessed different developing phases and revolutionary repercussions in the agriculture sector that has swayed the Islamic world and other secular agrarian systems. The Food security of a country depends on its Agriculture sector. Past records show that Malaysia, which is currently known to be the hub of Islamic Finance is facing serious threat in its food security and is undergoing unstable production of domestic food crops. From the composite view of Islamic Finance and Agriculture sector, the latter is unnoticed and is marginalized by the former. The principle objective of this research is to identify the challenges and prospects of Islamic Agriculture finance based on an organizational study on AgroBank, the sole agriculture bank in Malaysia that aims to transform into a full-fledged Islamic bank by 2015. A qualitative research methodology is applied to collect data from selected top management executives of AgroBank and academicians of Islamic Finance. The research findings shows that the bank has an opportunity to introduce new Islamic financing products and the core challenges related to it are upholding Shari'ah compliancy and mitigating various risks through new financing instruments. Being incorporated as a government linked company is the main growth prospect for the bank to transform into a new system besides large human capital and widespread branches around the country. This study is expected to raise heed on Islamic agriculture finance and add a standard value to the existing literature.